The impact of impulsive voltage waveforms on the electrical insulation of actuators for more electrical aircraft (MEA) - Cavallini, Andrea; Lusaurdi, Luca; Degano, Michele (2017)
To reduce the size and weight of aircraft actuators, wide band-gap semiconductor devices (SiC and GaN) are the most promising solution. These devices have switching times well below those of silicon devices. Very short rise times may enhance the electrical stress within the insulation, triggering partial discharges (PDs). The inception of PDs at carrier frequencies of several tens of kHz can lead to the premature failure of the actuator insulation, sometimes in the matter of minutes. In this paper, we show the results of PD measurements at different frequencies and pressures, and discuss the influence of both frequency and pressure on the inception of PDs. Our measurements show a steady decrease of RPDIV with the frequency up to 100 kHz, and a linear dependence of RPDIV on pressure. These findings can be useful to design reliable actuators.